Oxynoemacheilus phasicus, a new nemacheilid loach from the eastern Black Sea basin with some remarks on other Caucasian Oxynoemacheilus (Teleostei: Nemacheilidae) - Freyhof, Jörg; Kaya, Cüneyt; Epitashvili, Giorgi; Geiger, Matthias F. (Zootaxa, 2021)
Oxynoemacheilus phasicus, new species, is described from the Rioni and Enguri River drainages in Georgia. It is distinguished from other Oxynoemacheilus species in the O. brandtii group by a mottled or marbled flank pattern in adults, a slightly emarginate caudal fin, and a deep caudal peduncle. Molecular data suggest that the new species is characterized by a minimum K2P distance of 7.5% from O. brandtii from the Kura drainage in the mtDNA COI barcode region. Oxynoemacheilus brandtii and O. elsae are re-diagnosed. A very slender Oxynoemacheilus from the Aras drainage clusters as sister to O. elsae in our molecular analysis and not with O. brandtii from the Kura River. However, it is identified as O. brandtii as it is indistinguishable from this species in morphological characters.